The role of single nucleotide polymorphisms, contained in proinflammatory cytokine genes, in the development of congenital infection with human cytomegalovirus in fetuses and neonates. (April 2017) - Wujcicka, Wioletta; Wilczyński, Jan; Paradowska, Edyta; Studzińska, Mirosława; Nowakowska, Dorota
Abstract: Purpose: The research project targeted the distribution of genotypes, alleles and haplotypes in single nucleotide polymorphisms (SNPs) within the interleukin ( IL ) 1A, IL1B, IL6, IL12B and TNFA genes, in fetuses and neonates, congenitally infected with human cytomegalovirus (HCMV), and among uninfected controls. Methods: The study included 20 fetuses and neonates with congenital HCMV infection and 31 control individuals. The genotypes in SNPs of the studied cytokine genes were identified by a self-designed nested PCR-RFLP assays. Selected genotypes, representing distinct variants in analyzed polymorphisms, were confirmed by sequencing. The relationship between the genetic status of the studied polymorphisms and congenital infection development was estimated, using a logistic regression model. Results: The CT haplotype, composed of C allele determined in IL1A  −889 C > T and T allele in IL1B  +3954 C > T SNP, increased the risk of congenital HCMV infection, as well as the onset of disease related symptoms ( P  ≤ 0.0001). Considering disease outcome, the risk of development of symptoms, was increased among the CT heterozygotes in IL1A  −889 C > T polymorphism (OR 2.86, 95% CI 0.24–33.90; P  = 0.045). Moreover, multiple-SNP variants CCGAG in the range of all the SNPs, analyzed in the study, increased the risk of congenital infection with HCMV (OR 7.94, 95% CI 1.38–45.69; P  = 0.026). Conclusions: Polymorphisms within the proinflammatory cytokine genes may contribute to the development of congenital infection with HCMV. Highlights: CT haplotype in IL1A  −889 and IL1B  +3954 increase risk of congenital HCMV infection. CT haplotype in IL1A  −889 and IL1B  +3954 increase risk of symptomatic cytomegaly. CT heterozygosity in IL1A  −889 C > T SNP increases risk of symptomatic cytomegaly. Multiple-SNP variants in IL1A, IL6, IL12B and TNFA increase risk of HCMV infection. Polymorphisms in proinflammatory cytokine genes contribute to congenital cytomegaly.